The Importance of Behavioral Economics during COVID-19 - Cifuentes-Faura, Javier (Journal of Economics and Behavioral Studies, 2020)
Behavioral Economics seeks to understand the environments where decisions are made and to build proposals to optimize them. It offers the possibility to improve the design of public policies and, therefore, to enhance their results. The appearance of COVID-19 has caused thousands of deaths and millions of infected people around the world. This article describes the main behavioral biases that people exhibit during this pandemic. In order to curb the number of infections and stop the panic, it is essential to use Behavioral Economics tools, such as those proposed in this paper, to design messages that are simple and that motivate appropriate changes in human behavior. This work shows the importance of transmitting information correctly, of being aware of our own biases and that individual responsibility is fundamental to get out of this crisis.